Tuning of Li-argyrodites ionic conductivity through silicon substitution (Li6+xP1-xSixS5Cl0.5Br0.5) and their electrochemical performance in lithium solid state batteries. (20th December 2021) - Subramanian, Yuvaraj; Rajagopal, Rajesh; Senthilkumar, Baskar; Park, Yong Joon; Kang, Sung; Jung, Yu Jin; Ryu, Kwang-Sun
Highlights: Silicon substituted Li-argyrodite was successfully prepared using dry ball milling process. Li6.2 P0.8 Si0.2 S5 Cl0.5 Br0.5 electrolyte exhibited the high ionic conductivity of 5.12 mS cm −1 . The si substitution increased the volume of the unit cell thus facilitates to fast Li-ion transport. The prepared solid electrolyte has good electrochemical stability and compatibility with lithium. Our fabricated solid state battery showed high reversible capacity of 148 mAh g −1 at 0.1 c. Abstract: Lithium solid state batteries are one of the state of the art energy storage systems due to their high safety. However, ionic conductivity in solid electrolytes is a concern, because at present it does not match the ionic conductivity of non-aqueous Li-ion batteries, thus resulting in sluggish electrochemical kinetics. In this report, we enhance the ionic conductivity of Li-argyrodites (Li6 PS5 Cl0.5 Br0.5 ) through Si substitution at the P-site using a dry ball milling process. Among the silicon substitutions, Li6.2 Si0.2 P0.8 S5 Cl0.5 Br0.5 exhibited the high ionic conductivity of 5.12 mS cm −1 compared to pristine Li6 PS5 Cl0.5 Br0.5 at 4.02 mS cm −1 . The Rietveld refinement analysis revealed that after silicon substitution, volume of the unit cell gets increased that allows the lithium at T2-site, that promotes the fast Li-ion transport. Moreover, the optimized solid electrolyte was utilized in a solid state battery system, and demonstrated a high initial capacity of 148.1 mAh g −1 at 0.1 C rate compared to pristine argyrodite (135.1 mAh g −1 ). Further, we demonstrated the interface phenomena between electrode and solid electrolyte using ex-situ XPS analysis. This confirmed the formation of interface products such as LiCl, Li2 S, lithium polysulfides and P2 Sx, which influence the cycling stability of the ASSLBs. Graphical abstract: Image, graphical abstract